Hubungan Antara Adversity Quotient dengan Prestasi Kerja pada Account Officer di PT. PBR Harta Swadiri dan Grup - Mas’udah, Lizam; Nastiti, Dwi (Web of Scientist International Scientific Research Journal, 2024)
This study aims to determine and provide an explanation of the relationship adversity quotient with work performance on account officers at PT. PBR Independent Assets and Groups. The method of this research is quantitative with 156 account officer employees as subjects. The determination of subjects uses a saturated sampling technique in which all members of the population are taken as samples. The variables in this study are adversity quotient and work performance. Collecting data in this study used an adversity quotient scale made by researchers with a Likert scale model and work performance. The hypothesis in this study is that there is a positive relationship between the adversity quotient and work performance. Data analysis in this study used product moment correlation statistical tests with the help of SPSS 18 for Windows. The results of this study indicate that there is a positive relationship between the adversity quotient and the work performance of account officers at PT. BPR Self and Group Assets with a value of r = 0.438 with a significance value of 0.000 (P <0.05). This means that the higher the adversity quotient owned by the account officer, the higher the work performance produced and vice versa, the lower the adversity quotient owned, the lower the work performance.